I'm an ASTRONOMER now! - Stassun, Keivan Guadalupe (Singapore : WS Education, 2021)
"What is an astronomer? What does he or she do? Meet Keivan, a kid like you and me, who grew up and became an astronomer! As a child, Keivan was always interested in learning about planets orbiting other stars and this interest has taken him to the stars! Learn more about how he became involved in a space mission, as part of his research on exoplanets. The Who Me? series features inspirational biographies of scientists who young readers will be able to identify with as people like themselves. Written by the scientists themselves and co-authors from Vanderbilt University, the books are designed to help young readers understand that scientists are regular people like themselves who are excited about learning and discovering new things and who decided to work hard in school in order to create for themselves the opportunity to become scientists. As they learn the stories of these scientists, readers will also learn some basic science ideas that are well-explained and easily understood, and be introduced to the cutting-edge science these scientists are working on today"--Back cover
Keywords: Astronomers -- biography; Astronomy -- Juvenile literature